At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To isolate \( f \) in the equation \(\frac{1}{u} = \frac{1}{f} - \frac{1}{v}\), we will follow a series of algebraic steps.
1. Initial Equation:
[tex]\[ \frac{1}{u} = \frac{1}{f} - \frac{1}{v} \][/tex]
2. Combine the right-hand side over a common denominator:
To combine the terms \(\frac{1}{f}\) and \(\frac{1}{v}\), we need a common denominator:
[tex]\[ \frac{1}{f} - \frac{1}{v} = \frac{v - f}{fv} \][/tex]
Therefore, the equation becomes:
[tex]\[ \frac{1}{u} = \frac{v - f}{fv} \][/tex]
3. Equate the two fractions:
Since both sides are fractions, we can equate the numerators:
[tex]\[ \frac{1}{u} = \frac{v - f}{fv} \][/tex]
4. Cross-multiply to clear the fractions:
To clear the fractions, multiply both sides by \( u \cdot fv \):
[tex]\[ fv = u(v - f) \][/tex]
5. Distribute \( u \) on the right-hand side:
[tex]\[ fv = uv - uf \][/tex]
6. Group terms involving \( f \) on one side:
Add \( uf \) to both sides to isolate terms involving \( f \):
[tex]\[ fv + uf = uv \][/tex]
Factor out \( f \) on the left-hand side:
[tex]\[ f(v + u) = uv \][/tex]
7. Solve for \( f \):
Divide both sides by \( v + u \):
[tex]\[ f = \frac{uv}{u + v} \][/tex]
Thus, the subject \( f \) is:
[tex]\[ f = \frac{uv}{u + v} \][/tex]
1. Initial Equation:
[tex]\[ \frac{1}{u} = \frac{1}{f} - \frac{1}{v} \][/tex]
2. Combine the right-hand side over a common denominator:
To combine the terms \(\frac{1}{f}\) and \(\frac{1}{v}\), we need a common denominator:
[tex]\[ \frac{1}{f} - \frac{1}{v} = \frac{v - f}{fv} \][/tex]
Therefore, the equation becomes:
[tex]\[ \frac{1}{u} = \frac{v - f}{fv} \][/tex]
3. Equate the two fractions:
Since both sides are fractions, we can equate the numerators:
[tex]\[ \frac{1}{u} = \frac{v - f}{fv} \][/tex]
4. Cross-multiply to clear the fractions:
To clear the fractions, multiply both sides by \( u \cdot fv \):
[tex]\[ fv = u(v - f) \][/tex]
5. Distribute \( u \) on the right-hand side:
[tex]\[ fv = uv - uf \][/tex]
6. Group terms involving \( f \) on one side:
Add \( uf \) to both sides to isolate terms involving \( f \):
[tex]\[ fv + uf = uv \][/tex]
Factor out \( f \) on the left-hand side:
[tex]\[ f(v + u) = uv \][/tex]
7. Solve for \( f \):
Divide both sides by \( v + u \):
[tex]\[ f = \frac{uv}{u + v} \][/tex]
Thus, the subject \( f \) is:
[tex]\[ f = \frac{uv}{u + v} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.